Feasibility of steel fiber-reinforced self-compacting concrete containing recycled aggregates – compliance with EFNARC guidelines - Ali Mardani; Daniel Hatungimana; Naz Mardani; Joseph Assaad; Hilal El-Hassan (International Journal of Sustainable Engineering)
This paper assesses the effect of recycled concrete aggregate (RCA) on the fresh and hardened properties of fibre-reinforced self-compacting concrete (FRSCC) mixtures, including compliance with the workability criteria established by the European Guidelines. Tested mixtures contained fixed brass-coated steel fibres of 0.55% and targeted slump flow of 710 ± 20 mm, while the natural coarse limestone aggregates were gradually replaced by RCA at 20% increment rates, up to 100%. The mechanical strengths, transport properties, and durability are determined and compared to allowable thresholds adopted by the concrete industry. Test results showed that the ease of concrete deformation and capacity to pass through obstacles gradually curtailed with RCA additions, given the rougher aggregate surfaces that generate increased internal friction within the concrete skeleton and reinforcing bars. The European Guidelines for viscosity and passing ability can be achieved if the RCA replacement rate does not exceed 60% to 80%. The RCA addition rates should, however, be limited to 60% to maintain the drop in mechanical strengths and durability to less than 20%. A series of regression analyses and comparisons to existing literature are established, which can be of interest to engineers promoting the use of RCA in the FRSCC mixtures.